Rapeseed Oil Monoester of Ethylene Glycol Monomethyl Ether as a New Biodiesel. (20th February 2011) - Dayong, Jiang; Xuanjun, Wang; Shuguang, Liu; Hejun, Guo
Abstract : A novel biodiesel named rapeseed oil monoester of ethylene glycol monomethyl ether is developed. This fuel has one more ester group than the traditional biodiesel. The fuel was synthesized and structurally identified through FT-IR and P 1P H NMR analyses. Engine test results show that when a tested diesel engine is fueled with this biodiesel in place of 0# diesel fuel, engine-out smoke emissions can be decreased by 25.0%–75.0%, CO emissions can be reduced by 50.0%, and unburned HC emissions are lessened significantly. However, NOx emissions generally do not change noticeably. In the area of combustion performance, both engine in-cylinder pressure and its changing rate with crankshaft angle are increased to some extent. Rapeseed oil monoester of ethylene glycol monomethyl ether has a much higher cetane number and shorter ignition delay, leading to autoignition 1.1 ° CA earlier than diesel fuel during engine operation. Because of certain amount of oxygen contained in the new biodiesel, the engine thermal efficiency is improved 13.5%–20.4% when fueled with the biodiesel compared with diesel fuel.